A phase 2, randomized trial evaluating the combination of dalantercept plus axitinib in patients with advanced clear cell renal cell carcinoma. Issue 14 (5th April 2019) - Voss, Martin H.; Bhatt, Rupal S.; Vogelzang, Nicholas J.; Fishman, Mayer; Alter, Robert S.; Rini, Brian I.; Beck, J. Thaddeus; Joshi, Monika; Hauke, Ralph; Atkins, Michael B.; Burgess, Earle; Logan, Theodore F.; et al.
Abstract : Background: In a prior open‐label study, the combination of dalantercept, a novel antiangiogenic targeting activin receptor‐like kinase 1 (ALK1), plus axitinib was deemed safe and tolerable with a promising efficacy signal in patients with advanced renal cell carcinoma (RCC). Methods: In the current phase 2, randomized, double‐blind, placebo‐controlled study, patients with clear cell RCC previously treated with 1 prior angiogenesis inhibitor were randomized 1:1 to receive axitinib plus dalantercept versus axitinib plus placebo. Randomization was stratified by the type of prior therapy. The primary endpoint was progression‐free survival (PFS). Secondary endpoints were PFS in patients with ≥2 prior lines of anticancer therapy, overall survival, and the objective response rate. Results: Between June 10, 2014, and February 23, 2017, a total of 124 patients were randomly assigned to receive axitinib plus dalantercept (59 patients) or placebo (65 patients). The median PFS was not found to be significantly different between the treatment groups (median, 6.8 months vs 5.6 months; hazard ratio, 1.11 [95% CI, 0.71‐1.73; P =  .670]). Neither group reached the median overall survival (hazard ratio, 1.39 [95% CI, 0.70‐2.77; P =  .349]). The objective response rate was 19.0% (11 of 58 patients; 95% CI, 9.9%‐31.4%) in the dalantercept plus axitinib group and 24.6% (15 of 61 patients; 95% CI, 14.5%‐37.3%) in the placebo plus axitinib group. At least 1 treatment‐emergent adverse event of ≥grade 3 was observed in 59% of patients (34 of 58 patients) in the dalantercept group and 64% of patients (39 of 61 patients) in the placebo group. One treatment‐related death occurred in the placebo plus axitinib group. Conclusions: Although well tolerated, the addition of dalantercept to axitinib did not appear to improve treatment‐related outcomes in previously treated patients with advanced RCC. Abstract : In this randomized phase 2 study, patients with clear cell renal cell carcinoma who were treated with prior angiogenesis inhibitors were randomized 1:1 to receive axitinib plus dalantercept versus axitinib plus placebo. Although tolerance was comparable, the study did not reach its primary endpoint of improving progression‐free survival in the investigational versus the placebo arm.